Luminous emptiness : understanding the Tibetan book of dead - Fremantle, Francesca (Boston : London : Shambhala, 2003)
"In Luminous Emptiness, Francesca Fremantle presents the classic Tibetan Book of the Dead not as a scripture to be read to the dying but as a guide for the living. Fremantle, who worked closely with Chogyam Trungpa on the 1975 translation of the original text, brings the expertise of a lifetime of study to rendering this intriguing classic more accessible and meaningful."--Jacket.
Includes notes and index.
Keywords: Intermediate state -- Buddhism; Death -- Religious aspects -- Buddhism; Buddhist funeral rites and ceremonies